STUDY OF INFLUENCE OF BIOPREPARATE «MICROFIT» FOR THE CONDITION INTERNAL ORGANS OF LABORATORY RATS - Zakarya , K.D.; Sarmurzina , Z.S; Dospaeva , R.T.; Bissenova , G.N.; Shulgau , Z.T.; Gulyaev , A.E.; Krivoruchko , T.N.; Zhetpisbaev , B.B. (Eurasian Journal of Applied Biotechnology, 2017)
The article describes experimental results of preclinical tests of the combined biopreparation “Microfit” intended for prevention and correction of intestinal microflora. The preparation consists of lactic acid bacteria of the genus Lactobacillus, an extract of balsamic poplar and tagansorbent. Pre-clinical study of the safety of the biopreparation “Microfit” on the state of internal (absolute and relative mass) organs of laboratory animals was conducted. According to the results, it was established that the biopreparation “Microfit” with the course of intragastric rat administration to rats at the conventional therapeutic dose (30 mg/kg) and the dose 10 times higher than the conventional therapeutic dose (300 mg/kg) had not led to a general toxic and destructive effect on the internal organs of animals. The safety of the biopreparation “Microfit” after intragastric administration and good tolerance of animals was confirmed. The results allow approving safety of the tested biological product.